2008
DOI: 10.1371/journal.pone.0002667
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes from Cystic Fibrosis Patients Are Locked in an LPS Tolerance State: Down-Regulation of TREM-1 as Putative Underlying Mechanism

Abstract: Cystic Fibrosis (CF) is an inherited pleiotropic disease that results from abnormalities in the gene that codes for the chloride channel, Cystic Fibrosis Transmembrane Conductance Regulator (CFTR). CF patients are frequently colonized by several pathogens, but the mechanisms that allow colonization in spite of apparently functional immune systems are incompletely understood. In this paper we show that blood peripheral monocytes isolated from CF patients are found in an endotoxin tolerance state, yet this is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 59 publications
2
85
0
2
Order By: Relevance
“…Although the underlying mechanisms implicated in ET have been extensively studied, including reprogrammed epigenetic, microRNAs, and several molecules (1,7,27,28), a complete picture of this process is still lacking. In-depth studies of ET have analyzed the participation of a number of factors and have established the role of several negative regulators, such as IRAK-M, ST2, suppressor of cytokine signaling 1, short version of MyD88 and SHIP, as well as the dysregulation of TLR4 and TREM-1 (4,12,29,30), roles that have been observed occasionally in different models (1,9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the underlying mechanisms implicated in ET have been extensively studied, including reprogrammed epigenetic, microRNAs, and several molecules (1,7,27,28), a complete picture of this process is still lacking. In-depth studies of ET have analyzed the participation of a number of factors and have established the role of several negative regulators, such as IRAK-M, ST2, suppressor of cytokine signaling 1, short version of MyD88 and SHIP, as well as the dysregulation of TLR4 and TREM-1 (4,12,29,30), roles that have been observed occasionally in different models (1,9).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating cells isolated from patients with sepsis show a reduced capacity to produce proinflammatory cytokines when stimulated with an endotoxin ex vivo (3,4). ET has also been observed for other pathologies such as acute coronary syndrome (5) and cystic fibrosis (6)(7)(8).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…TREM-1 was shown to be expressed at low levels in lung resident macrophages and circulating monocytes from CF patients. This phenomena was associated with a failure to mount an appropriate inflammatory response, 67,68 along with an impairment of antigen presentation properties. Those monocytes expressed elevated levels of PU.1, a transcription factor that counteracts the TLRs-induced TREM-1 upregulation.…”
Section: Effects Of the Trem-1 Pathway Modulation During Inflammatorymentioning
confidence: 99%
“…Monocytes are a major source of TREM-1 in inflammation (Arts et al, 2011;Cavaillon, 2009;Ferat-Osorio et al, 2009;Wong-Baeza et al, 2006) and their expression has been shown to be regulated in several bacterial and fungal infections, including infections of the respiratory track, gut or amniotic fluid (Aoki et al, 2004;Begum et al, 2004;Buckland et al, 2011;del Fresno et al, 2008;How et al, 2011;Kusanovic et al, 2011;Richeldi et al, 2004;Schmausser et al, 2008). Individual microbial components, such as lipopolysaccharide (LPS) and peptidoglycan, can cause up-regulation of cell surface-localized TREM-1 by monocytes, as well as release in its soluble (s)TREM-1 form (Begum et al, 2004;Gibot et al, 2004b;Gomez-Pina et al, 2007;Murakami et al, 2007;Ramanathan et al, 2005;Zeng et al, 2007).…”
Section: Introductionmentioning
confidence: 99%